Brazil Country Program Evaluation, FY2004-11 : Evaluation of the World Bank Group Program - Independent Evaluation Group (Washington, DC: World Bank, 2014)
This country program evaluation (CPE) evaluates World Bank Group (International Bank for Reconstruction and Development (IBRD), or the Bank, International Finance Corporation (IFC), and Multilateral Investment Guarantee Agency (MIGA) operations in Brazil from FY2004 through FY2011. It seeks to answer two questions: to what extent was the Bank Group program relevant to Brazil's development needs?, and how effective were Bank Group operations in helping to accelerate economic growth and making growth more inclusive and environmentally sustainable? The period reviewed was covered by two country strategies, one for FY2004-07 and the other for FY2008-11. The evaluation comments on aspects of the country partnership strategy (CPS) FY2012-15 with particular reference to its relevance and design. The report aims to extract lessons relevant to future Bank Group operations in Brazil. The study also examines the synergies between lending and knowledge services and the effectiveness of collaboration within the Bank Group and with external development partners. This report has five chapters. Chapter one gives purpose and country context. Chapter two summarizes the Bank Group operations and examines trends and patterns during the evaluation period. Chapters three and four assess the relevance and contributions of these operations to the objectives stated in the country strategies. The concluding chapter draws lessons and recommendations for the Bank Group's future engagement in Brazil.